2011
DOI: 10.1038/jp.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of erythromycin and UDCA in premature infants during parenteral nutrition in minimizing feeding intolerance and liver function abnormalities

Abstract: Objective: To compare the effectiveness of oral erythromycin versus ursodeoxycholic acid (UDCA) treatment in preventing feeding intolerance and liver function abnormalities.Study Design: A prospective, double blind, randomized, controlled trial in which three groups of preterm infants (birth weight <1500 g) were randomized to erythromycin (12.5 mg kg À1 per day), UDCA (5 mg kg À1 every 6 h) or placebo treatment. During the period 352 infants were admitted to our unit of which 75 infants whose parents accepted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…In a retrospective study of non-surgical very low birth weight infants with cholestasis on long-term PN, UDCA was associated with shortened course of cholestasis and decreased peak serum bilirubin level compared with historical controls 55 . In another trial of very low birth weight infants, UDCA was associated with a lower incidence of GGT elevation than placebo, but interestingly there was no difference in bilirubin and aminotransferase levels 56 . UDCA use is sometimes limited by diarrhea, which could be a concern in children with SBS.…”
Section: Ursodeoxycholic Acidmentioning
confidence: 94%
“…In a retrospective study of non-surgical very low birth weight infants with cholestasis on long-term PN, UDCA was associated with shortened course of cholestasis and decreased peak serum bilirubin level compared with historical controls 55 . In another trial of very low birth weight infants, UDCA was associated with a lower incidence of GGT elevation than placebo, but interestingly there was no difference in bilirubin and aminotransferase levels 56 . UDCA use is sometimes limited by diarrhea, which could be a concern in children with SBS.…”
Section: Ursodeoxycholic Acidmentioning
confidence: 94%
“…In particular the content of taurine in the amino acid solution (0.3 g/100 ml; Aminopaed 10%; Fresenius Kabi, Graz, Austria, EU) and the nature of lipid emulsion (exclusively soybean oil based; Intralipid 20%, Fresenius Kabi, Graz, Austria, EU) did not change. In both periods, urodeoxycholic acid was used for treatment—but not prevention ( Gokmen et al, 2012 )—of PNAC. Infants did not receive erythromycin ( Aly et al, 2007 ; Gokmen et al, 2012 ; Ng et al, 2007 ) to reduce time until full enteral feeds.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent ESPGHAN position paper [519] early EN is recommended limiting i. v. lipid to 15e30 % of non-protein energy provided by PN and cyclic administration of PN once the patient is stable. The use of ursodeoxycholic acid (UDCA) and erythromycin has been reported to facilitate EN in premature infants on PN [520]. The authors of the ASPEN clinical guidelines analyzed seven publications on this issue and found a very low level of evidence for a beneficial role of UDCA in the treatment of PNAC [488].…”
Section: Commentarymentioning
confidence: 99%